Image Processing Marker Augmented Reality For Design Furniture Room - Sri Desy Siswanti; Titoyan Titoyan (Annual Research Seminar (ARS), 2015)
AR useful for industrial applications to enhance the visual perception of the user, for example, the AR system is capable of visually new building project at a real construction site, which gives the viewer a better understanding in accordance with the existing environment. The method used by the AR is a marker detection and tracking, the method used for the detection and tracking marker is a natural feature tracking. This method detects features that are in the marker. In detecting marker object sometimes can not appear because of the influence of several factors: the size of the marker printing, color printing conditions marker and the environment when making a marker by the camera (light), therefore, in this study analyze the AR marker colors for the design of indoor furniture. Marker marker colors used are 8-bit RGB color brochure with a picture size of 496 x 702 pixels with a marker print size 210 x 148.5 mm and 297 x 420 mm. On testing took 6 print condition marker, where the marker is placed in a room print then the camera will detect in real-time to print the marker. In the data processing using the histogram and star-rating as an indicator of the possibility marker can be detected. Based on testing and data processing, then that marker print size, print condition marker and marker detection affects the environment when the object visualization.